Mechanisms of Hamstring Injury in Professional Soccer Players: Video Analysis and Magnetic Resonance Imaging Findings - Jokela, Aleksi (My University, 2023)
Hamstring injuries are very common and responsible of a large portion of time lost from competition in different sports requiring high speeds with rapid acceleration and deceleration. Two different hamstring injury mechanisms have been previously described in the literature: stretching and sprinting-type. Stretching-type injuries usually affect the proximal semimembranosus, while sprinting-type injuries typically cause proximal biceps femoris injuries. This study was a descriptive case series of 14 consecutive professional soccer players. All athletes suffered an acute hamstring injury between September 2017 and January 2022. After the injuries, the accurate diagnosis was confirmed by MRIs. For the purposes of this study, specific injury mechanisms were systematically analyzed by the authors based on video footage with allowance for slow motion and video stoppage. Two authors filled a standardized questionnaire developed for hamstring injuries to categorize injuries. The main aim of the study was to describe the injury mechanisms and their relation to magnetic resonance imaging (MRI) findings in acute hamstring injuries among male soccer players. Playing situation, player/opponent behavious, movement, biomechanical body positions, and MRI injury location were analyzed. Based on our results, most hamstring injuries in soccer occur during high-speed movements. In addition to stretch-type (36%) and sprint-type (21%), also mixed-type (43%) injury mechanisms occurred, which included patterns from both sprinting and stretching. The most typical actions were change of direction, kicking, and running. Most frequent body positions at defined injury moments were neutral trunk (43%), hip flexion 45°-90° (57%), and knee flexion <45° (93%). MRI findings showed that 79% were isolated single-tendon injuries, isolated proximal femoris injury being the most common injury type.
Keywords: hamstring, muscle injuries, injury mechanism, video analysis, magnetic resonance imaging, single-tendon